Self-expandable metal stents for obstructing colonic and extracolonic cancer: European Society of Gastrointestinal Endoscopy (ESGE) Guideline – Update 2020 - van Hooft, Jeanin E.; Veld, Joyce V.; Arnold, Dirk; Beets-Tan, Regina G.H.; Everett, Simon; Götz, Martin; van Halsema, Emo E.; Hill, James; Manes, Gianpiero; Meisner, Soren; Rodrigues-Pinto, Eduardo; Sabbagh, Charles; Vandervoort, Jo; Tanis, Pieter J.; Vanbiervliet, Geoffroy; Arezzo, Alberto (Endoscopy, 2020)
The following recommendations should only be applied after a thorough diagnostic evaluation including a contrast-enhanced computed tomography (CT) scan.1 ESGE recommends colonic stenting to be reserved for patients with clinical symptoms and radiological signs of malignant large-bowel obstruction, without signs of perforation. ESGE does not recommend prophylactic stent placement.Strong recommendation, low quality evidence.2 ESGE recommends stenting as a bridge to surgery to be discussed, within a shared decision-making process, as a treatment option in patients with potentially curable left-sided obstructing colon cancer as an alternative to emergency resection.Strong recommendation, high quality evidence.3 ESGE recommends colonic stenting as the preferred treatment for palliation of malignant colonic obstruction.Strong recommendation, high quality evidence.4 ESGE suggests consideration of colonic stenting for malignant obstruction of the proximal colon either as a bridge to surgery or in a palliative setting.Weak recommendation, low quality evidence.5 ESGE suggests a time interval of approximately 2 weeks until resection when colonic stenting is performed as a bridge to elective surgery in patients with curable left-sided colon cancer.Weak recommendation, low quality evidence.6 ESGE recommends that colonic stenting should be performed or directly supervised by an operator who can demonstrate competence in both colonoscopy and fluoroscopic techniques and who performs colonic stenting on a regular basis.Strong recommendation, low quality evidence.7 ESGE suggests that a decompressing stoma as a bridge to elective surgery is a valid option if the patient is not a candidate for colonic stenting or when stenting expertise is not available.Weak recommendation, low quality evidence.